What happened at Megiddo?: Josiah's death as described in the book of Kings - Aviʿoz, Mikhaʾel (Biblische Notizen, 2009)
Scholars who have studied the story of Josiah’s death in 2Kgs 23:29-30 discussed various questions that arise therefrom: Did a battle between Josiah and the king of Egypt take place also according to the account in Kings? Is the Chronicles Version based on the Kings version, or is it taken from another source? This article deals solely with the first question. Our objective is to show that based on the account in Kings as well as Chronicles, Josiah died in battle. To that end, we propose a new analysis of the Kings account of Josiah’s death, without discussing that in Chronicles.